A pesca artesanal no litoral do estado do Ceará e sua relação com o Programa Agroamigo - Reis, Rubens de Oliveiros dos (2024)
Artisanal fishing is fundamental for coastal communities in Ceará, contributing to the generation of income and food security, covering 20 coastal municipalities that explore marine fishing, using relatively simple equipment and selling the product with the work of intermediaries. This activity is considered the main source of production in these communities, developing significant effort in socioeconomic and cultural terms, especially for communities that fight for conditions that harmonize with their lifestyle. Focusing on artisanal fishing in Ceará, this study is divided into two chapters in the format of articles, with the objective of the first to investigate the dynamism of fishing activity, resorting to the use of secondary sources, with the use of information already in progress, drawing on from the Maritime Extractive Fishing Database in the State of Ceará in 2021. The results of the work show the basic fishing infrastructure available in the municipalities, the vessels used, types of equipment used in the activity, indicating those of the vessels, species captured and the average selling price of fish, revealing the importance of fishing not only as an economic activity, but also as an essential element of the cultural identity and daily life of coastal communities. The second chapter starts from the premise that fishermen face challenges in accessing the necessary financing for the sustainable development of the activity. Obtaining adequate credit is essential for maintaining artisanal fishing, but the lack of tangible guarantees and the seasonality of fishing activity make access to credit difficult. In this context, the Agroamigo Program, created by the Federal Government in partnership with Banco do Nordeste, supports artisanal fishing, offering financing to small producers and fishermen. Given the socioeconomic importance of the activity, the study aims to analyze the evolution of financing for artisanal fishing from 2005 to 2022, using, for this purpose, data from Banco do Nordeste, stratified to cover the 20 municipalities coastal areas belonging to the State of Ceará, and where fishermen, the central target of the study, access credit through the National Program for Strengthening Family Agriculture. The results demonstrate that, although significant, the program's performance is still low for most of the municipalities analyzed. Given its importance for the development of artisanal fishing, challenges were identified that need to be faced and overcome to ensure an equitable distribution of resources and a sustainable improvement in the living conditions of artisanal fishermen.